Tathwiiru Tharzi Al Masyruu'i Al Asaasiyyi Al Ta'allumiyyi Bi Mabdai Al Ahliyyati Al Tiknulujiyyati Li Tahsiini Kafaaati Kitaabati Al Lughah Al Arabiyyati Wa Ibdaa'i Al Fikri - Rifda Haniefa; Eka Lutfiyatun (University of Darussalam Gontor, 2023)
Arabic writing skills in the modern era are not only done with conventional media such as paper and blackboards, but also are applied with the help of digital media which is one of the pillars of digital literacy. Arabic language learning at SMP Nurussalam Depok is carried out in a language laboratory, but the use of laboratory computers is still limited only as a provider of material and has not been used for making projects that can optimize Arabic writing competence and hone students' creativity. Creative Thinking becomes urgent in modern times. Improving creative thinking and writing Arabic can be done by implementing Project Based Learning (PjBL). The research problems are how to develop a digital literacy-based PjBL model to optimize Arabic writing skills and creative thinking, its validity, and its effectiveness. The aims are to find out the form of digital literacy-based PjBL model development to optimize Arabic writing competence and creative thinking, find out the results of its validity, and find out its effectiveness. This research is a Research and Development (R&D) which the data comes from tests, questionnaires, and observations. The research subjects were 20 students of class IX at SMP Nurussalam Depok. Product validation value is 88.33 (very feasible). The PjBL model based on digital literacy is effective in optimizing Arabic writing competence and creative thinking. The average pretest<posttest is 67.85<89.90 with a significance of 0.00<0.05. The average value of creative thinking is 82.22 or very suitable for the uniqueness of ideas, meaningful product creation, process suitability, and motivation. Hopefully educators can develop and utilize the models that have been developed for learning. Keywords: Project Based Learning Model, Digital Literacy, Arabic Writing, Creative Thinking في هذا العصر الراهن، مهارة كتابة اللغة العربية ليست تنحصر في الوسائط التقليدية فحسب، مثل الكتابة في الورقة، أو السبورة، وإنما تنصرف أيضا تلك المهارة في الوسائط التكنولوجية التي قد أصبحت عمدة من عماد إتقان الكتابة التكنولوجية.جرى تعليم اللغة العربية في المدرسة الثانوية